2020
DOI: 10.1093/omcr/omaa089
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent giant phyllodes tumour in a 17-year-old female: a rare case report

Abstract: Phyllodes tumours (PTs) are rare fibroepithelial tumours of the breast with incidence accounting for <1% in the general population. Availability of reports on PTs with size of 31 cm or more in diameter in the literature are extremely rare. Herein, the case of a 17-year-old female patient with a giant recurrent right breast PT is reported. Histologically, the tumour showed proliferation of stromal tumour cells consisting of spindle cells with uniform nuclear chromatin, inconspicuous nucleoli, abundant eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…First it will tell us histologically that it is phylloides and not otherwise and second it will give malignance status of the phylloides which can be benign, borderline or malignant. For this case it was confirmed phylloides tumor and was benign [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…First it will tell us histologically that it is phylloides and not otherwise and second it will give malignance status of the phylloides which can be benign, borderline or malignant. For this case it was confirmed phylloides tumor and was benign [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 90%
“…A systematic review and meta-analysis study done by Lu et al in China reported the pooled local recurrence rates for benign, borderline and malignant patients to be 8, 13 and 18%, respectively. This shows that the tendency of patients to recur locally increases with increase in aggressiveness of the tumor [ 1 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 A review of the literature reveals only 20 published cases of PTs in adolescents. 1,11 Of those existing reports, only one describes the reconstructive approach following mastectomy. 12 That case differs from ours in that the patient had reached full skeletal maturity and complete breast development at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These are fast growing tumors and can reach a median size of 4 cm and sometimes can grow up to 50 cm. 3 Mammography shows round densities with smooth borders and is distinguishable from fibroadenoma. Phyllodes tumor were classified as benign (70%), borderline (15%), or malignant (15%) based on histologic tumor characteristics i.e., cellular atypia, stromal overgrowth, tumor margins, tumor necrosis and mitotic count.…”
Section: Introductionmentioning
confidence: 99%